New-onset Systemic Lupus Erythematosus presenting with Macrophage Activation Syndrome and Diffuse Alveolar Hemorrhage: a case-based review - Calheiros Cruz, Gonçalo; Sousa, Mariana; Vilela, Sara; Gouveia, Rita (Brazilian Journal of Case Reports, 2022)
Macrophage activation syndrome is a form of secondary hemophagocytic lymphohistiocytosis in the setting of autoimmune diseases. It’s a rare, hyperinflammatory complication requiring prompt institution of therapy to prevent organ dysfunction and death. We report a young female presenting with macrophage activation syndrome with multiorgan failure and diffuse alveolar hemorrhage in the setting of inaugural systemic lupus erythematosus. The patient was successfully treated with steroids, plasma exchange and cyclophosphamide.